KAJIAN TATA LAYOUT DAN FASILITAS KERJA DOSEN TELKOM UNIVERSITY KASUS STUDI : RUANG KERJA DOSEN FIK TELKOM UNIVERSITY - Doddy Friestya Asharsinyo; Ully Irma Maulina Hanafiah (Ide dan Dialog Desain Indonesia (Idealog), 2018)
The quality and performance of lecturers apart from the quality of their education, are also obtained from the surrounding academic environment, which is related to the workspace environment in conducting Tridarma activities. The lecturer workspace is Tridarma's activities take place, it is also a space for lecturers to actualize themselves through their fields of expertise, science and works. The layout of the lecturers' workplaces related to scientific fields at the Faculty of Creative Industries differs from one another, due to the results of work activities, research carried out, and the resulting paperwork varies from dimension / size in the field of expertise / science. The standard of work space for lecturers in general is the same for all fields of science. This research method is carried out with a qualitative approach, starting by observing empirical facts about the working space of the lecturers in the Faculty of Creative Industries, and then explaining the existing conditions and analyzing in accordance with applicable standards. The results & findings of this study conclude that the activity patterns and layout in the Tel-U lecturer workspace at the Faculty of Creative Industry are associated with the field of knowledge of each study program have the same cubical pattern and facilities, with a centralized orientation circulation in the middle of the room, there is no no special work storage space.